2012
DOI: 10.1038/modpathol.2012.61
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and molecular features of sporadic early-onset colorectal adenocarcinoma: an adenocarcinoma with frequent signet ring cell differentiation, rectal and sigmoid involvement, and adverse morphologic features

Abstract: Recent literature suggests an increasing incidence of colorectal carcinoma in young patients. We performed a histologic, molecular, and immunophenotypic analysis of patients with sporadic early-onset (r40 years of age) colorectal carcinoma seen at our institution from the years 2000-2010 and compared these tumors to a cohort of consecutively resected colorectal carcinomas seen in patients 440 years of age. A total of 1160 primary colorectal adenocarcinomas were surgically resected for the years 2000 through 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
216
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(255 citation statements)
references
References 34 publications
18
216
4
4
Order By: Relevance
“…10,13,14 Parallel with the previous studies, in the current study age and sex were shown not to have any significant effect on survival. 12,15,16 As opposed to a study suggesting that female sex had a worse effect on survival, it was found in the current study that there were no differences in survival between sexes. Although there are various data concerning the size of tumors in the literature, it was suggested that well-and moderately-differentiated carcinomas might be diagnosed at larger sizes (5.5-6.2 cm).…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…10,13,14 Parallel with the previous studies, in the current study age and sex were shown not to have any significant effect on survival. 12,15,16 As opposed to a study suggesting that female sex had a worse effect on survival, it was found in the current study that there were no differences in survival between sexes. Although there are various data concerning the size of tumors in the literature, it was suggested that well-and moderately-differentiated carcinomas might be diagnosed at larger sizes (5.5-6.2 cm).…”
Section: Resultscontrasting
confidence: 54%
“…In line with the former publications, we diagnosed most signet ring cell cancers at advanced stages. 7,[11][12][13][14][15][16][17] Data published concerning lymphatic and vascular invasions are generally heterogeneous. In accordance with Tung et al 13 and Makino et al, 17 in our series metastasis tended to develop in lymph nodes and on peritoneal surfaces rather than in the liver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Of the patients with a hereditary cancer syndrome, one third were diagnosed with LS and one third had mutationnegative LS. Six patients with mutation-negative LS had incomplete work-ups for several reasons; therefore, we suspect that the number of patients with CRC who had mutation-positive LS could be higher than what is reported here.…”
Section: Wwwjcoorgmentioning
confidence: 99%
“…The foregoing conditions represent the most common of the known hereditary crc (hcrc) syndromes, with lifetime risks for crc as high as 80% for ls and approaching 100% for map and fap when left untreated 8 . Three additional groups at high risk for crc or polyposis include families with familial colorectal cancer type X 9 , families with unexplained polyposis 10 , and people diagnosed with crc at very young ages (≤40 years) 11 . Although the genetic causes in each of these groups is unclear, hcrcrs play a large role in the identification and characterization of high-risk families, in gene discovery efforts, and in determining the best available clinical management 9,10,12,13 .…”
Section: Terms Of Referencementioning
confidence: 99%